Applications of molecular diagnostics for personalized treatment of head and neck cancer: state of the art. (1st February 2016) - Mes, Steven W.; Leemans, C. René; Brakenhoff, Ruud H.
ABSTRACT: Squamous cell carcinomas of the head and neck are the sixth most frequent tumors worldwide. Risk factors are carcinogenic exposure, infection with the human papillomavirus (HPV) and genetic predisposition. Lymph node metastasis in the neck and HPV status are major prognostic factors. There are several important clinical challenges that determine the research agenda in head and neck cancer. The first is more accurate staging, particularly of occult metastatic lymph nodes in the neck. A second challenge is the lack of biomarkers for personalized therapy. There are a number of treatment modalities that can be employed both single and in combination, but at present only site and stage of the tumor are used for treatment planning. Provided here is an overview of the successes and failures of molecular diagnostic approaches that have been and are being evaluated to address these clinical challenges.